A rigid and healable polymer cross-linked by weak but abundant Zn(II)-carboxylate interactions - Lai, Jian-Cheng (Nat Commun, 2018)
Achieving a desirable combination of solid-like properties and fast self-healing is a great challenge due to slow diffusion dynamics. In this work, we describe a design concept that utilizes weak but abundant coordination bonds to achieve this objective. The designed PDMS polymer, crosslinked by abundant Zn(II)-carboxylate interactions, is very strong and rigid at room temperature. As the coordination equilibrium is sensitive to temperature, the mechanical strength of this polymer rapidly and reversibly changes upon heating or cooling. The soft–rigid switching ability σ, defined as G’(max) /G’(min), can reach 8000 when ΔT = 100 °C. Based on these features, this polymer not only exhibits fast thermal-healing properties, but is also advantageous for various applications such as in orthopedic immobilization, conductive composites/adhesives, and 3D printing.